Response of the wheat mycobiota to flooding revealed substantial shifts towards plant pathogens - Francioli, Davide; Cid, Geeisy; Hajirezaei, Mohammad-Reza; Kolb, Steffen (Frontiers in Plant Science, 2022)
Rainfall extremes are intensifying as a result of climate change, leading to increased flood risk. Flooding affects above- and belowground ecosystem processes, representing a substantial threat to crop productivity under climate change. Plant-associated fungi play important roles in plant performance, but their response to abnormal rain events is unresolved. Here, we established a glasshouse experiment to determine the effects of flooding stress on the spring wheat-mycobiota complex. Since plant phenology could be an important factor in the response to hydrological stress, flooding was induced only once and at different plant growth stages, such as tillering, booting and flowering. We assessed the wheat mycobiota response to flooding in three soil-plant compartments (phyllosphere, roots and rhizosphere) using metabarcoding. Key soil and plant traits were measured to correlate physiological plant and edaphic changes with shifts in mycobiota structure and functional guilds. Flooding reduced plant fitness, and caused dramatic shifts in mycobiota assembly across the entire plant. Notably, we observed a functional transition consisting of a decline in mutualist abundance and richness with a concomitant increase in plant pathogens. Indeed, fungal pathogens associated with important cereal diseases, such as Gibberella intricans, Mycosphaerella graminicola, Typhula incarnata and Olpidium brassicae significantly increased their abundance under flooding. Overall, our study demonstrate the detrimental effect of flooding on the wheat mycobiota complex, highlighting the urgent need to understand how climate change-associated abiotic stressors alter plant-microbe interactions in cereal crops.